The Intracellular Location and Function Of Proteins Of Neuronal Ceroid Lipofuscinoses - Ezaki, Junji (Brain Pathol, 2006)
Neuronal ceroid lipofuscinoses are a group of diseases characterized by accumulation of hydrophobic proteins in lysosomes of neurons and other types of cells. NCLs are caused by at least 8 mutant genes (CLN1 CLN8), though CLN4 and CLN7 have not yet been identified. Except for Cln1p, the protein encoded by CLN1, the defective proteins are associated with lysosomal accumulation of mitochondrial ATP synthase subunit c Cln1p and Cln2p are soluble lysosomal enzymes, targeted to lysosomes in a mannose 6‐phosphate dependent manner. Mutations in the lysosomal protease cathepsin D cause another NCL. Cln3p, Cln5p, Cln6p and Cln8p are thought to be transmembrane proteins. Cln3p and Cln5p are localized in the endosome‐lysosomal compartment. Deficiency of endosomal membrane protein CLC‐3, a member of the chloride channel family, causes NCL‐like phenotype and lysosomal storage of subunit c. Herein, we review the features of NCL and NCL‐related proteins and discuss the involvement of the proteins in lysosomal degradation of subunit c.